2018
DOI: 10.1126/scisignal.aah6692
|View full text |Cite
|
Sign up to set email alerts
|

The channel-kinase TRPM7 regulates antigen gathering and internalization in B cells

Abstract: Members of the transient receptor potential (TRP) family of ion channels are cellular sensors involved in numerous physiological and pathological processes. We identified the TRP subfamily M member 7 (TRPM7) channel-kinase as a previously uncharacterized regulator of B cell activation. We showed that TRPM7 played a critical role in the early events of B cell activation through both its ion channel and kinase functions. DT40 B cells deficient in TRPM7 or expressing a kinase-deficient mutant of TRPM7 showed defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 56 publications
(94 reference statements)
0
23
0
Order By: Relevance
“…Krishnamoorthy et al [ 121 ] took advantage of NS8593 to demonstrate that TRPM7 controls antigen internalization and presentation in B cells. The DT40 B cell line deficient in the TRPM7 gene was unable to aggregate antigen after activation likely due to abnormal phospholipase C (isoform γ2) signalling and altered lipid metabolism.…”
Section: Ns8593 As a Tool To Investigate The Function Of Trpm7 Curmentioning
confidence: 99%
“…Krishnamoorthy et al [ 121 ] took advantage of NS8593 to demonstrate that TRPM7 controls antigen internalization and presentation in B cells. The DT40 B cell line deficient in the TRPM7 gene was unable to aggregate antigen after activation likely due to abnormal phospholipase C (isoform γ2) signalling and altered lipid metabolism.…”
Section: Ns8593 As a Tool To Investigate The Function Of Trpm7 Curmentioning
confidence: 99%
“…Studies showing the effect of disturbances in Mg 2+ homeostasis on the mechanisms of differentiation, proliferation, and maturation of hematopoietic cells in the bone marrow are rare, and there are few references in recent decades about this topic, whereby the majority of the results were obtained only in experimental models [ 15 ]. These studies demonstrated the impact of Mg 2+ deficiency on peripheral blood cells [ 4 , 5 ] or on the lymphocyte maturation process, as well as on thrombopoiesis, with a focus on the transient receptor potential cation channel subfamily M member 7 (TRPM7) channel [ 16 , 17 ]. Several studies raised the importance of intracellular Mg 2+ homeostasis via the TRPM7 channel, which in addition to being permeable to Mg 2+ , is also permeable to Ca 2+ and Zn 2+ , relevant for processes such as growth, survival, differentiation, and cell migration [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently identified an important role for TRPM7 in regulating the actin cytoskeleton and consequently several early events in B‐cell activation . We demonstrated that deletion of TRPM7 in DT40 B cells led to cytoskeletal defects both at resting state and upon activation, as TRPM7‐KO B cells exhibited elongated filopodia‐like protrusions, but reduced lamellipodia when cells are adhered to glass.…”
Section: Ion Channels In Early B‐cell Activation and Synapse Formationmentioning
confidence: 91%
“…TRPM7 is a non‐selective cation channel that has been implicated in calcium influx and store recovery upon BCR stimulation, as well as Mg 2+ homeostasis . We recently identified a key role for both the channel and kinase functions of TRPM7 in BCR signaling and activation . We found that both TRPM7‐KO and kinase‐dead (KD) DT40 B cells have increased and sustained ERK phosphorylation upon BCR stimulation.…”
Section: Ion Channels In Bcr Activation and Signalingmentioning
confidence: 91%